HUBUNGAN PENYESUAIAN DIRI DENGAN KECEMASAN KOMUNIKASI MAHASISWA PAUD STKIP AISYIYAH RIAU - Septia Ningsih Ningsih; Daviq Chairilsyah Chairilsyah; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Phenomenon that occurs on studentsof early childhood education of STKIPAisyiyahare there are students whofeel scared, worried, and he sitated when expressing opinions during discussionsin class. This condition makes the student withdraws from the interaction, do not want to engage in a conversation and just talk when they pressed. Most of the students failed to adjust to the new environment, so it tends to avoid unpleasant conditions. The communication anxiety of Early childhood education student at STKIP Aisyiyah shows the total score of each indicator of anxiety descriptively. The purpose of this study was to determine: (1) Self adjustment of early childhood students at STKIP Aisyiyah Riau, (2) Anxiety communication of early childhood students at STKIP Aisyiyah Riau, and (3) The relationship between the self adjustment and anxiety of communication on early childhood students STKIP Aisyiyah Riau. The study population of early childhood students at STKIP Aisyiyah Riau is who are third semester and the total sample is 31 people. Data collection techniques used was namely questionnaire. The hypothesis of this study is that there is a singnifikan relationship between the self adjustmentwith anxietycommunicationof early childhood education at STKIP Aisyiyah Riau. The results of the analysis of data obtained by the tcount of 3.348 while the value ttabel 2,000 (5%) (df = n - 2 = 31-2 = 29), so thitung> ttable or 3.348> 2.000. This means that there is a significant relationship between the selfadjustment with anxiety communication. The resulting determinant coefficient is r2 = 0.278 to P = 0.000 (P <0.05). This means that the self adjustment gives effect of 27.8%. The level of relationship between the adjustment to the anxiety of communication included in the low category with coefficient of 0.278. Key Words: Self Adjustment, Anxiety of Communication